Respuesta :

caylus
Hello,

Answer C

125x^6-8=(5x²)^3-2^3=(5x²-3)((5x²)²+2*5*x²+4)

Answer:

[tex](5x^2-2)(25x^4+10x^2+4)[/tex]

Step-by-step explanation:

Given expression,

[tex]125x^6-8[/tex]

[tex]=(5)^3 (x^2)^3 -2^3[/tex]    [tex]\because (ab)^m=a^mb^m\text{ and }a^{mn}=(a^m)^n[/tex]

[tex]=(5x^2)^3+(-2)^3[/tex]

By using a³ + b³ = (a-b) (a² -ab + b² )

[tex]=(5x^2+(-2)) ((5x^2)^2 - (5x^2\times -2) + (-2)^2)[/tex]

[tex]=(5x^2-2)(25x^4+10x^2+4)[/tex]

Which is the required factor form,

Third option is correct.